ANALISIS SISTEM PENGENDALIAN MANAJEMEN UNTUK MENINGKATKAN KINERJA MELALUI KERJA SAMA PADA PERUSAHAAN INTRA UNIT - Triyono Triyono; Tabah Rizki; Arina Hidayati; Islamiyah (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study investigates the relationship between management control systems and cooperation, which translates into the performance of intra-organizational relationships. This study aims to test a theoretical model using Partial Least Square (PLS) on survey data collected from the retail industry sector. This quantitative research uses a survey method by collecting data using random sampling techniques. The sample used in this study was taken from the respondents of managers and supervisors who have authority in purchasing or procuring goods in the store or warehouse. Next, the questionnaire is organized into two parts; the first contains demographic data, and the next is long-term work, which will be loaded into 20 questions. The results show a direct relationship between performance measurement systems and the three dimensions of cooperation (information sharing, problem-solving, and willingness to adapt to change. This study examines the influence of the performance measurement system and the socialization process on business units' performance, where cooperation plays a mediating variable. The results of this study make a significant contribution by explaining the role of this growing knowledge pool by empirically exploring how cooperation can be mobilized and enforced through SPM, performance measurement systems, and socialization processes